COVID-19 impact on the brazilian stock market - Vitor Gonçalves de Souza (Contextus – Revista Contemporânea de Economia e Gestão, 2024)
Background: The COVID-19 pandemic caused unprecedented disruptions globally, impacting public health, economies, and financial markets. Governments responded with emergency measures and economic stimulus packages to mitigate the crisis's effects. The rationale behind this study lies in understanding the Brazilian stock market reactions to extreme events and specific interventions, which is crucial for policymakers and investors, especially in emerging markets reliant on stability and foreign capital. Purpose: This research aims to identify how the Brazilian stock market responded to the uncertainties created by the COVID-19 pandemic and whether the economic stimulus package offered by the Brazilian authorities restored confidence in the market. Method: Using event study methodology, we examined the impact of COVID-19 on the Brazilian stock market, focusing on different economic sectors, ownership structures, and company factors. Our analysis covers four major events: the declaration of COVID-19 as a Public Health Emergency of International Concern (PHEIC) and a pandemic, as well as two economic stimulus announcements. The sample comprised companies listed on B3 with daily trading in 2019, totaling 150 companies/stocks. Results: The result suggest that Covid-19 affected the economic sectors in different ways, with the hotels, restaurants, travel and leisure services being the most affected in Brazil. The findings indicate that the declaration of COVID-19 as a pandemic appears to have the greatest impact on stock returns and the return of less leveraged firms was less affected. Regarding stimulus packages, only the announce of the emergency package had a significant positive impact on equity returns. Conclusions: This research shows that distinct events, positive or negative, have different impact on stocks and markets' performance, mainly regarding to economic sectors, size, ownership, profitability and event windows.